Immunomodulatory Mechanism of Acyclic Nucleoside Phosphates in Treatment of Hepatitis B Virus Infection. Issue 5 (7th February 2020) - Murata, Kazumoto; Tsukuda, Senko; Suizu, Futoshi; Kimura, Akihiro; Sugiyama, Masaya; Watashi, Koichi; Noguchi, Masayuki; Mizokami, Masashi
Abstract : Background and Aims: Current treatment with nucleos(t)ide analogs (NUCs) safely controls the replication of hepatitis B virus (HBV) and improves prognosis in patients with HBV. However, the inability to completely clear HBV is problematic, and novel therapies are desired. It has been believed that all NUCs have similar functions to inhibit HBV reverse transcriptase. However, our recent findings that only acyclic nucleoside phosphonates (ANPs; adefovir dipivoxil and tenofovir disoproxil fumarate) had an additional effect of inducing interferon (IFN)‐λ3 in the gastrointestinal tract suggests that ANPs are not only distinct from nucleoside analogs (lamivudine and entecavir) in their structures but also in their functions. Because enteric lipopolysaccharide (LPS) can cross the intestine and affect peripheral blood mononuclear cells (PBMCs), we hypothesized that orally administered ANPs could have further additional effects to modulate LPS‐mediated cytokine profile in PBMCs. Approach and Results: This study showed that pretreatment of PBMCs, from either healthy volunteers or patients with HBV, with ANPs inhibited LPS‐mediated interleukin (IL)‐10 production, which reciprocally induced IL‐12p70 and tumor necrosis factor‐α production in a dose‐dependent manner. Furthermore, the combination of IFN‐α and ANPs synergistically enhanced LPS‐mediated IL‐12p70 production in PBMCs. Mechanistic analyses revealed that cellular metabolites of ANPs directly bound the Akt protein, inhibiting its translocation to the plasma membrane, thereby impairing Akt phosphorylation. Therefore, pretreatment of PBMCs with ANPs impairs LPS‐mediated IL‐10 production. Conclusions: Among NUCs, only ANPs have an additional pharmacological effect modulating LPS‐mediated cytokine production, which is expected to produce favorable immune responses toward HBV elimination. This additional immunomodulation by ANPs in PBMCs, as well as IFN‐λ3 induction in the gastrointestinal tract, provides insights into HBV treatment.